1998
DOI: 10.1096/fasebj.12.6.487
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin B4regulates human monocyte/neutrophil adherence and motility: design of stable lipoxin B4analogs with increased biologic activity

Abstract: Lipoxins are biologically active products of arachidonic acid that are formed via cell-cell interactions, particularly those involving leukocytes. Lipoxin A4 and lipoxin B4 (LXB4), within similar concentration ranges, each inhibit human neutrophil, activate monocyte adherence and motility, and are rapidly converted by initial dehydrogenation to other inactive metabolites by human monocytes. Here, we exposed LXB4 to isolated recombinant 15-hydroxy-prostaglandin dehydrogenase (15-PGDH) and found that it was a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Furthermore, the aspirin-triggered 15-epi-LXB 4 and the stable LX analogue 15(R/S)-methyl-LXA 4 (19) also stimulated phagocytosis. The enhanced efficacy and stability of LX analogues in modulation of leukocyte trafficking in models of inflammation and second organ injury after local and systemic administration has led to the proposal that these compounds might have therapeutic potential (17)(18)(19)(20). Consistent with this are our data that highlight the attractiveness of LX stable analogues, which are resistant to metabolic inactivation by monocytes/macrophages yet retain the activity of the native LX (17,19,21).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the aspirin-triggered 15-epi-LXB 4 and the stable LX analogue 15(R/S)-methyl-LXA 4 (19) also stimulated phagocytosis. The enhanced efficacy and stability of LX analogues in modulation of leukocyte trafficking in models of inflammation and second organ injury after local and systemic administration has led to the proposal that these compounds might have therapeutic potential (17)(18)(19)(20). Consistent with this are our data that highlight the attractiveness of LX stable analogues, which are resistant to metabolic inactivation by monocytes/macrophages yet retain the activity of the native LX (17,19,21).…”
Section: Discussionsupporting
confidence: 75%
“…The rapid metabolic degradation of native LX by dehydrogenation at C15 and possibly -oxidation at C20 has prompted the design and synthesis of stable analogues, which retain many of the properties of the native LX, including inhibition of PMN adhesion and transmigration (17,4). In a cytokine primed milieu, the catalytic activity of aspirin-acetylated cyclooxygenase type 2 (COX-2) is shifted from a cyclooxygenase to 15R lipoxygenase.…”
mentioning
confidence: 99%
“…Changes in intracellular Ca 2+ by release of cytosolic Ca 2+ and influx of extra cellular Ca 2+ effect leukocyte chemotaxis, modulation of adhesion molecules and elaboration of arachiodonic metabolites including prostaglandins, leucotrines and lipoxins. [38][39][40][41] These latter agents influence the inflammatory process and leukocyte adhesion. Prostaglandins are also involved in the pathogenesis of pain and fever in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduction of the 15-oxo group by 15-PGDH yields 13,14-dihydro-LXA 4 , revealing an additional catalytic activity for this enzyme (11). LXB 4 can also be dehydrogenated by 15-PGDH at carbon 5 to produce 5-oxo-LXB 4 , therefore sharing a common route of inactivation (12). It has recently been shown that 15-oxo-LXA 4 is also produced from LXA 4 in mouse whole blood (13), suggesting that the mouse shares with humans a common pathway for LXA 4 inactivation.…”
Section: Mechanisms Of Inactivationmentioning
confidence: 99%